Add-On Energy Harvesting of Diesel Exhaust Muffler Using Thermoelectric Generator - Aditya Wahyu Winadi Atmajaya; Purbo Suwandono (Widyagama University of Malang, 2023)
Trends Light fossil fuel vehicles are now turning to electricity. The electric vehicle transition begins with a hybrid car. The Hybrid vehicle uses an internal combustion engine as a generator. Controller systems, driving safety and entertain light vehicles are growing so that they consume a lot of electricity, Safe devices and driving lifestyle support. An additional battery charging system for a hybrid car now is being developed by the automotive manufacturer at least the system can increase the fulfilment of electricity consumption needs.The charging system can utilize waste energy vehicle itself or even from outside the vehicle system. In this research, the author wants to explore the thermal energy harvesting system in the remaining exhaust gases. The concept of this research is to develop a Thermoelectric Generator (TEG) as a power producer. The heat source uses a 140kW diesel engine with a heat potential of 523K at stationary conditions, and an exhaust velocity of 1407.05 m / s. This study demonstrates the potential prototype TEG then compared Ansys simulation and manual calculations as the first step for further research. The results obtained, the Exhaust TEG can produce a voltage of 2.1 Volt at 30 seconds of data collection. The cooling system on the TEG exhaust from the HVAC cooler with a temperature of 289K and a Velocity of 0.8 can produce a significant temperature difference.Keywords: Diesel Engine, Thermoelectric, Exhaust TEG system, Electricity.